Assessing interaction quality in Arabic online discussion forums - Zainuddin, Nurkhamimi (2011)
This paper reports on a study, based on an extensive review of current literature in related areas, as a way forward in looking at the assessment of quality in Arabic online discussion forums (AODF). The paper will assess the interaction quality in AODF based on the criteria introduced by Henri (1992), Newman et al. (1996) and Garrison et al. (2001). The study showed that interaction was effectively facilitated through the use of text-based forums, and that participants used the online interaction to build a learning community and to generate knowledge within the learning community. Results indicated that participants engaged primarily in processes related to “clarification and critical assessment”, and did not reach a satisfied stage of “critical discussions of contributions”. The main benefits of the proposed criteria are towards facilitators, as a way to assess learners’ online contributions, while students may use it to understand what is expected of them as participants in online discussion forums.